Narrowing the energy efficiency gap: The impact of educational programs, online support tools and energy-related investment literacy - Julia Blasch; Massimo Filippini; Nilkanth Kumar; Adan Martinez-Cruz (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
There is evidence that many individuals make sub-optimal investment decisions when the benefits and costs associated with that decision are distributed over time. One example is the decision to adopt new electrical appliances, with the benefits of choosing a more energy efficient device materializing only in the future. This paper analyses the impact of the level of an individual's energy-related investment literacy on the adoption of energy-efficient appliances. Moreover, the empirical analysis explores the impact of decision support tools such as educational slides on the probability that individuals identify the appliance with the lowest lifetime cost, which is ideally also the most energy-efficient appliance. To test the influence of these decision support tools, we developed an online randomized controlled trial and implemented it on two independently chosen samples of the Swiss population. One treatment offers a short education program on how to calculate the lifetime cost of an appliance – via a set of information slides. The second intervention provides access to an online calculator that supports the investment decision-making of the individual. Results across the two samples are encouraging. We find that i) pre-treatment energy and investment literacy positively impact on the probability of identifying the appliance with the lowest lifetime cost; ii) the reinforcement of energy-related investment literacy increases the rate at which individuals identify the appliance with the lowest lifetime cost; and iii) while both interventions are effective in increasing the chances that an appliance with the lower lifetime cost is chosen, the online calculator turned out to be more effective than the educational program. Public policy implications are discussed.
Keywords: D12; D80; Q41; Q48; 330; energy-efficient appliances; energy-related investment literacy; appliance choice; bounded rationality; educational programs; online tool